Conservatism of Nikolai Berdyaev: freedom to transform tradition - Makarova Anna F. (Вестник Свято-Филаретовского института, 2023)
The article is an analytical review of the views of the Russian philosopher Nikolai Berdyaev on the problem of conservatism, understanding the reality of the historical Orthodox Church and analysis of some subjects that are at the intersection of these two fields. The author proposes to answer three questions: 1) What is Berdyaev-style conservatism? 2) How should such conservatism manifest itself in the church life (or it should not)? 3) What could be the role of the philosopher in these processes? In the article, Berdyaev’s specific interpretation of conservatism is indicated: for him conservatism is the freedom to change (transform) tradition while maintaining connection with the Fathers; such creative processes, according to the philosopher, should also take place in the church, and the role of a thinker, a believing philosopher in this can be important — that was shown by Berdyaev himself and by the heroes of his articles, which became the causes or expression of conflicts between Berdyaev and the Orthodox Church: “Quenchers of the Spirit” (1913), “The Worth of Christianity and the Unworthiness of Christians” (1928), “The Spirit of the Grand Inquisitor” (1935) and “Does freedom of Thought and Conscience exist in Orthodoxy? (In defense of Georgy Fedotov)” (1939). The article concludes that in Berdyaev’s thought there is a paradoxical but stable combination of free-reform and proOrthodox sentiments, reinforced by an explicit anti-revolutionary position — not only political, but also ideological.